Magneto-LED therapy in the treatment of inflammatory lesions and erosions of the glans penis - case report - Jarosław Pasek; Tomasz Pasek; Grzegorz Cieślar; Aleksander Sieroń (Termedia Publishing House, 2016)
Introduction . Inflammatory lesions and erosions of the glans penis defined as balanitis or balanoposthitis constitute a disease in which the effectiveness of conservative treatment is not sufficient. Objective. To present the therapeutic efficacy of magneto-LED therapy in the treatment, and to present a patient with inflammatory lesions and erosions of the glans penis. Case report. The patient, 68 years old with inflammatory lesions and erosions of the glans penis of 2-4 years duration, was previously treated with various methods of local therapy without effect. As a result of a 32-week long magneto-LED therapy cycle, complete resolution of skin lesions with subsidence of the burning sensation during urination and reduced swelling and inflammatory erythema of the glans, as well as disappearance of the white coating and unpleasant smell, was achieved. Conclusions . Magneto-LED therapy is an efficient method of treatment of inflammatory lesions and erosions of the glans penis.